Selecting The Best Broiler Chicken Supplier of PT Sentral Unggas Perkasa Using Analytical Hierarchy Process and Weighted Product Methods - Yuniar Farida; Putri Krismadewi; Dian Yuliati; Hani Khaulasari (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
PT SUP is one of the companies engaged in trading broiler chicken products. Supplying broiler chickens to PT SUP sometimes results in product instability, and some conditions are inadequate; the financing process is not by income or obstacles that occur when serving customers. So this can disappoint the customers of PT SUP. This study aims to select suppliers for 4 out of 6 breeders chosen as the best suppliers and will get a reward from PT SUP to improve the performance and product results of the suppliers. The selection of the best supplier is based on the criteria that have been owned, namely Based on Curriculum Vitae (CV), location of the cage, capital, and service. The six suppliers come from 3 (each city has two suppliers), namely Lumajang, Lamongan, and Kediri. In this study, the author uses the AHP (Analytic Hierarchy Process) method to produce a consistent value of comparison results. It can be continued with the WP (Weighted Product) approach to get the value of the V vector for ranking alternatives. PT SUP will beard the results of the selection of the best four suppliers. The best supplier of PT SUP are Y1, Y4, Y2 dan Y3. Combining these two methods is a form of contribution to the MCDM enrichment.